A Host-Oriented Inhibitor of Junin Argentine Hemorrhagic Fever Virus Egress - Lu, Jianhong; Han, Ziying; Liu, Yuliang; Liu, Wenbo; Lee, Michael S.; Olson, Mark A.; Ruthel, Gordon; Freedman, Bruce D.; Harty, Ronald N. (Journal of virology, 2014)
There are currently no U.S. Food and Drug Administration (FDA)-approved vaccines or therapeutics to prevent or treat Argentine hemorrhagic fever (AHF). The causative agent of AHF is Junin virus (JUNV); a New World arenavirus classified as a National Institute of Allergy and Infectious Disease/Centers for Disease Control and Prevention category A priority pathogen. The PTAP late (L) domain motif within JUNV Z protein facilitates virion egress and transmission by recruiting host Tsg101 and other ESCRT complex proteins to promote scission of the virus particle from the plasma membrane. Here, we describe a novel compound (compound 0013) that blocks the JUNV Z-Tsg101 interaction and inhibits budding of virus-like particles (VLPs) driven by ectopic expression of the Z protein and live-attenuated JUNV Candid-1 strain in cell culture. Since inhibition of the PTAP-Tsg101 interaction inhibits JUNV egress, compound 0013 serves as a prototype therapeutic that could reduce virus dissemination and disease progression in infected individuals. Moreover, since PTAP l -domain-mediated Tsg101 recruitment is utilized by other RNA virus pathogens (e.g., Ebola virus and HIV-1), PTAP inhibitors such as compound 0013 have the potential to function as potent broad-spectrum, host-oriented antiviral drugs. IMPORTANCE There are currently no FDA-approved vaccines or therapeutics to prevent or treat Argentine hemorrhagic fever (AHF). The causative agent of AHF is Junin virus (JUNV); a New World arenavirus classified as an NIAID/CDC category A priority pathogen. Here, we describe a prototype therapeutic that blocks budding of JUNV and has the potential to function as a broad-spectrum antiviral drug.